Experimental Approach to Developing Equatorial Soil Loss Equation - Samuel Lik Ging, Law; King Kuok, Kuok; S. G., Trinidad; Po Chan, Chiu; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri; Mei Yun, Chin (Journal of Hunan University Natural Sciences, 2022)
This paper aims to develop a soil loss equation used within an equatorial climate (2,300 – 6,000 mm of annual rainfall) and hilly terrain based on measured data from the experiment concerning measured erosion outcomes, called Equatorial Soil Loss Equation (EQSLE). The equation under development should consider high equatorial rainfall intensities and challenging topographical conditions, thus introducing the new factors – Equatorial Rainfall Erosivity Factor (Reqt-factor) and Equatorial Slope Length Factor (Leqt-factor). The process included a photogrammetric method and image processing for raindrop size distribution and an experimental plot setup for a length differential study. The final equation has the form of A=Reqt⸱Leqt⸱S⸱K⸱C⸱P for soil erosion estimation in the equatorial region with the involvement slope and hilly terrain. The performance of the Reqt-factor and Leqt-factor are evaluated using the experimental data, and works of literature are carried out for the results. The formation of the two factors has addressed the challenges of high rainfall intensities and extreme terrain conditions faced by Peninsular Malaysia and East Malaysia. In future work, more case studies on the performance of soil loss rate prediction should be conducted to improve the overall performance of EQSLE as well as the respective factors.